Identifying Financial Exclusion and Islamic Microfinance as An Alternative to Enhance Financial Inclusion - Maulana, Hartomi; Umam, Khoirul (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2017)
Even though the banking industry is growing exponentially, but they are still out of reach from the hardcore poor. The population under poverty remains financially excluded from the mainstream banking facilities. The aim of this paper is to examine the main factors that hinder customers to access financing from mainstream banking in Indonesia province of East Java using Exploratory Factor Analysis (EFA). The study also attempts to identify the possibility of Islamic microfinance, in this case Baitul Maal Tamwil, (BMT) as role of model in integrating commercial and social seeking which can be used as one of an alternative platform to enhance financial inclusion.  In quantitative data, the paper employs primary data collected by self-administered questionnaires involving a sample of 243 respondents. To explore the micro-entrepreneurs’ criteria of barrier access to finance, an exploratory factor analysis is employed. In qualitative data, a semi-structure interview used to generate information from the respondents. The interview covers the second objectives and involves seven experts in microfinance including practitioner and academicians.  The study reveals that, the religious factor is perceived as the most important factor to be considered as financing barriers factors, then followed by affordability, accessibility, eligibility, and availability factors. The study indicates that Islamic microfinance may be an alternative platform to integrate commercial and social objective in order to enhance financial inclusion.